PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN MENERAPKAN MODEL PROJECT CITIZEN DALAM PEMBANGUNAN KARAKTER MAHASISWA - Eko Priyanto (Khazanah Pendidikan, 2018)
The subject of Citizenship Education (PKn) is basically as charactereducation for students. The character of students as Indonesian citizens.Character values built on students are based on the conditions set by the Centerfor Curriculum of the Ministry of National Education, including: Religious,Honest, Tolerance, Discipline, Hard Work, Creative, Independent, Democratic,Curiosity, National Spirit, Love of the Motherland , Respect for Achievement,Friendly / Communicative, Love Peace, Love to Read, Care for the Environment,Social Care, and Responsibility. Research methods in this study include: Datacollection using: Interviews, observations, documentation. Data analysis,namely qualitative analysis with stages of data reduction, data display, and dataconclusions. The results of the study show that Civics Education learning usingthe Project Citizen model can build / instill the value of UMP student characters.The student character values include religious, creative, curiosity, hard work,democratic, responsibility, tolerance, respect for achievement, friendship/communicative, fond of reading, caring for the social and natural environment.Keywords: Character, Project Citizen, Citizenship Education